2018
DOI: 10.1007/s11356-018-2257-y
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-tunable tellurium nanomaterials produced by the tellurite-reducing bacterium Lysinibacillus sp. ZYM-1

Abstract: Although tellurite is highly toxic to organisms, elemental tellurium nanomaterials (TeNMs) have many uses. The microbe-mediated reduction of tellurite to Te(0) has been shown to be a green and cost-effective approach for turning waste into wealth. However, it is difficult to tune the morphology of biogenic nanomaterials. In this study, a series of experiments was conducted to investigate the factors influencing tellurite reduction by the tellurite-reducing bacterium Lysinibacillus sp. ZYM-1, including pH, tell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Most show a clear indication of the formation of Te (0) aggregates with different levels of structural organization. The formation of different structures of aggregates is indicative of different metabolic mechanisms involved in the formation of said structures, as is observed in previous works ( Wang et al., 2018 ). The strain B. altitudinis 3W19 appears to produce two morphologically distinct Te-containing structures.…”
Section: Discussionsupporting
confidence: 71%
“…Most show a clear indication of the formation of Te (0) aggregates with different levels of structural organization. The formation of different structures of aggregates is indicative of different metabolic mechanisms involved in the formation of said structures, as is observed in previous works ( Wang et al., 2018 ). The strain B. altitudinis 3W19 appears to produce two morphologically distinct Te-containing structures.…”
Section: Discussionsupporting
confidence: 71%
“…In some similar studies, MICs of 5 mM in Lysinibacillus sp. 34 , 6 mM in Pseudomonas pseudoalcaligenes 40 , 12 mM in Salinicoccus sp. 41 , and 13 mM in Escherichia sp.…”
Section: Resultsmentioning
confidence: 99%
“…EBL303. As far as we are aware, only one research has reported the Lysinibacillus genus's ability in tellurite reduction 34 , despite the fact that the phenol degradation ability of this genus is well known [35][36][37] .…”
Section: Resultsmentioning
confidence: 99%
“…Bioreduction is a relevant biotechnological characteristic to determine, as varies among different organisms; therefore, for new bacterial strains, the reduction efficiency should be determined. The bioreduction to Te can lead to the formation of nanostructures ( Baesman et al, 2007 ; Zare et al, 2012 ; Presentato et al, 2016 ; Wang et al, 2018 ). As verified for other metals, the formation of Te-containing intra-/extra-cellular nanostructures can be monitored by following the bioreduction process.…”
Section: Introductionmentioning
confidence: 99%